2018
DOI: 10.1002/adma.201801078
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Molecular Doping Mechanism in Organic Single‐Crystalline Semiconductors and their Application in Color‐Tunable Light‐Emitting Devices

Abstract: Organic single-crystalline semiconductors with long-range periodic order have attracted much attention for potential applications in electronic and optoelectronic devices due to their high carrier mobility, highly thermal stability, and low impurity content. Molecular doping has been proposed as a valuable strategy for improving the performance of organic semiconductors and semiconductor-based devices. However, a fundamental understanding of the inherent doping mechanism is still a key challenge impeding its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 99 publications
0
23
0
1
Order By: Relevance
“…Notably, compounds 1 and 2 also possess similar molecular packing patterns and effective energy level matching (Supplementary Fig. 15b ), giving rise to color-tunable 12 alloy assemblies 52 , 53 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Notably, compounds 1 and 2 also possess similar molecular packing patterns and effective energy level matching (Supplementary Fig. 15b ), giving rise to color-tunable 12 alloy assemblies 52 , 53 .…”
Section: Resultsmentioning
confidence: 97%
“…For instance, we found that the combination of 3 and 4 can assemble into binary alloy ribbons with variable composition 30 . Moreover, the material combination of 1 and 2 which show a similarity in molecular configuration and size can also form two-component alloys by substitution of 1 with a small molar ratio of 2 52 , 53 . While the combination of compounds 1 and 3 or 1 and 4 , may result in heterostructured or isolated particles in their phase separated state due to their obvious structural differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic semiconductor crystals (OSCCs) with intrinsic lack of defects and grain boundaries exhibit high charge transport efficiency, long exciton diffusion length, and lifetime, which has received ever‐increasing interest for optoelectronic device applications, such as organic field‐effect transistors (OFETs), organic light‐emitting diodes (OLEDs), organic photovoltaics (OPVs), and photodetectors . Over the past 30 years, impressive advancements in the carrier mobility of OSCCs have been achieved, as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…The most common building blocks found in these compounds are those of phenalenyl and thiazole, as well as some others . Although substitutional doping has been explored in some molecular materials, most often as a means to control their optical properties for light‐emitting devices as well as some other examples, its application to molecular radical conductors is still relatively new. Recently, the Haddon group has been exploring the effect of substitutional doping on phenalenyl‐based neutral radical conductors .…”
Section: Introductionmentioning
confidence: 99%